The game of urban regeneration. Culture & community in London 2012 and Berlin's Mediaspree. - Weber-Newth, Francesca (transcript, 2019)
Who wins and who loses in urban regeneration? What are the mechanisms at play? The author looks at two neighborhoods that are adjacent to large-scale regeneration schemes: the 2012 Olympic park in London and the Mediaspree waterside development in Berlin. By analyzing how urban regeneration is experienced on the ground, her study counters the notion that Olympic-led regeneration is any different from other forms of neoliberal urban development. Adopting Pierre Bourdieu's view of the social world as made up of competitive games, an analysis of the two neighborhoods reveals how the concepts of culture and community are strategically employed in the game of urban regeneration - to the benefit of some and the detriment of others.
Keywords: Stadterneuerung; Stadtentwicklungspolitik; Stadtquartier; Aufwertung; Stadtsoziologie; Kultur; Gesellschaft; Urbanismus; Nachbarschaft; Stadtbewohner; Verdrängung; Gentrifizierung; Städtevergleich